Synthesis, Characterization and Evaluation of Antimicrobial Activity for New Heterocyclic Derivatives Containing Pentagonal, HexagonalRings. - A.J Alfraiji, Redhab; M.H. Al-Majidi, Suaad (Iraqi Journal of Science, 2023)
This research, involved a series of some new compounds containing different hetero cyclic new pentagonal and hexagonal rings, through the reaction of 2-mercapto-3-phenyl-4(3H)quinazolinone (1) with chloroacetylchloride in the presence of potassium hydroxide, and dry dimethylformamide (DMF) as a solvent to obtain the intermediate compound (2). This compound is reacted with different reagents to give four routes, the first route include direct reaction with substituted-2-aminobenzothiazole under certain conditions to give new compounds (3-9). The second route involved condensation compound (2) with 5-substituted-2-amino-1,3,4-oxadiazole in the presence of potassium carbonate anhydrous to give new compounds (10-13).while the third route involved condensation compound (2) with para-phenylenediamine in ethanol as a solvent to give the corresponding compound (14) which the conversion new substitutes 1,2,3-triazole compounds (17-18) were prepared through the reaction of compound (14) with different reagent to give compounds (15-16). And subsequent reactions to obtain compounds (17-18) respectively. The fourth route include reaction compound (2) with para-chlorosulphonylaniline to give compound (19) which the conversion new sulphanilamide compounds (20-22) were prepared through the reaction compound (19) with different primary aromatic amine. The structure of newly synthesized compounds were identified by spectral methods their [FTIR,1HNMR, 13C-NMR] and measurements some of its physical properties and some specific reactions. Furthermore were studied the effects of the preparing compounds on some strains of bacteria and fungicidal.